How to use Loose-Parts in STEAM? Early Childhood Educators Focus Group discussion in Indonesia - Maria Melita Rahardjo (Jurnal Pendidikan Usia Dini, 2019)
In recent years, STEAM (Science, Technology, Engineering, Art, and Mathematics) has received wide attention. STEAM complements early childhood learning needs in honing 2nd century skills. This study aims to introduce a loose section in early childhood learning to pre-service teachers and then to explore their perceptions of how to use loose parts in supporting STEAM. The study design uses qualitative phenomenological methods. FGDs (Focus Group Discussions) are used as data collection instruments. The findings point to two main themes that emerged from the discussion: a loose section that supports freedom of creation and problem solving. Freedom clearly supports science, mathematics and arts education while problem solving significantly supports engineering and technology education.Keywords: Early Childhood Educators, Loose-part, STEAMReferences:Allen, A. (2016). Don’t Fear STEM: You Already Teach It! Exchange, (231), 56–59.Ansberry, B. K., & Morgan, E. (2019). Seven Myths of STEM. 56(6), 64–67.Bagiati, A., & Evangelou, D. (2015). Engineering curriculum in the preschool classroom: the teacher’s experience. European Early Childhood Education Research Journal, 23(1), 112–128. https://doi.org/10.1080/1350293X.2014.991099Becker, K., & Park, K. (2011). Effects of integrative approaches among science , technology , engineering , and mathematics ( STEM ) subjects on students ’ learning : A preliminary meta-analysis. 12(5), 23–38.Berk, L. E. (2009). Child Development (8th ed.). Boston: Pearson Education.Can, B., Yildiz-Demirtas, V., & Altun, E. (2017). The Effect of Project-based Science Education Programme on Scientific Process Skills and Conception of Kindergargen Students. 16(3), 395–413.Casey, T., Robertson, J., Abel, J., Cairns, M., Caldwell, L., Campbell, K., … Robertson, T. (2016). Loose Parts Play. Edinburgh.Cheung, R. H. P. (2017). Teacher-directed versus child-centred : the challenge of promoting creativity in Chinese preschool classrooms. Pedagogy, Culture & Society, 1366(January), 1–14. https://doi.org/10.1080/14681366.2016.1217253Clements, D. H., & Sarama, J. (2016). Math, Science, and Technology in the Early Grades. The Future of Children, 26(2), 75–94.Cloward Drown, K. (2014). Dramatic lay affordances of natural and manufactured outdoor settings for preschoolaged children.Dejarnette, N. K. (2018). Early Childhood Steam: Reflections From a Year of Steam Initiatives Implemented in a High-Needs Primary School. Education, 139(2), 96–112.DiGironimo, N. (2011). What is technology? Investigating student conceptions about the nature of technology. International Journal of Science Education, 33(10), 1337–1352. https://doi.org/10.1080/09500693.2010.495400Dugger, W. E., & Naik, N. (2001). Clarifying Misconceptions between Technology Education and Educational Technology. The Technology Teacher, 61(1), 31–35.Eeuwijk, P. Van, & Zuzana, A. (2017). How to Conduct a Focus Group Discussion ( FGD ) Methodological Manual.Flannigan, C., & Dietze, B. (2018). Children, Outdoor Play, and Loose Parts. Journal of Childhood Studies, 42(4), 53–60. https://doi.org/10.18357/jcs.v42i4.18103Fleer, M. (1998). The Preparation of Australian Teachers in Technology Education : Developing The Preparation of Australian Teachers in Technology Education : Developing Professionals Not Technicians. Asia-Pacific Journal of Teacher Education & Development, 1(2), 25–31.Freitas, H., Oliveira, M., Jenkins, M., & Popjoy, O. (1998). The focus group, a qualitative research method: Reviewing the theory, and providing guidelines to its planning. In ISRC, Merrick School of Business, University of Baltimore (MD, EUA)(Vol. 1).Gomes, J., & Fleer, M. (2019). The Development of a Scientific Motive : How Preschool Science and Home Play Reciprocally Contribute to Science Learning. Research in Science Education, 49(2), 613–634. https://doi.org/10.1007/s11165-017-9631-5Goris, T., & Dyrenfurth, M. (n.d.). Students ’ Misconceptions in Science , Technology , and Engineering .Gull, C., Bogunovich, J., Goldstein, S. L., & Rosengarten, T. (2019). Definitions of Loose Parts in Early Childhood Outdoor Classrooms: A Scoping Review. The International Journal of Early Childhood Environmental Education, 6(3), 37.Hui, A. N. N., He, M. W. J., & Ye, S. S. (2015). Arts education and creativity enhancement in young children in Hong Kong. Educational Psychology, 35(3), 315–327. https://doi.org/10.1080/01443410.2013.875518Jarvis, T., & Rennie, L. J. (1996). Perceptions about Technology Held by Primary Teachers in England. Research in Science & Technological Education, 14(1), 43–54. https://doi.org/10.1080/0263514960140104Jeffers, O. (2004). How to Catch a Star. New York: Philomel Books.Kiewra, C., & Veselack, E. (2016). Playing with nature: Supporting preschoolers’ creativity in natural outdoor classrooms. International Journal of Early Childhood Environmental Education, 4(1), 70–95.Kuh, L., Ponte, I., & Chau, C. (2013). The impact of a natural playscape installation on young children’s play behaviors. Children, Youth and Environments, 23(2), 49–77.Lachapelle, C. P., Cunningham, C. M., & Oh, Y. (2019). What is technology? Development and evaluation of a simple instrument for measuring children’s conceptions of technology. International Journal of Science Education, 41(2), 188–209. https://doi.org/10.1080/09500693.2018.1545101Liamputtong. (2010). Focus Group Methodology : Introduction and History. In Focus Group MethodoloGy (pp. 1–14).Liao, C. (2016). From Interdisciplinary to Transdisciplinary: An Arts-Integrated Approach to STEAM Education. 69(6), 44–49. https://doi.org/10.1080/00043125.2016.1224873Lindeman, K. W., & Anderson, E. M. (2015). Using Blocks to Develop 21st Century Skills. Young Children, 70(1), 36–43.Maxwell, L., Mitchell, M., and Evans, G. (2008). Effects of play equipment and loose parts on preschool children’s outdoor play behavior: An observational study and design intervention. Children, Youth and Environments, 18(2), 36–63.McClure, E., Guernsey, L., Clements, D., Bales, S., Nichols, J., Kendall-Taylor, N., & Levine, M. (2017). How to Integrate STEM Into Early Childhood Education. Science and Children, 055(02), 8–11. https://doi.org/10.2505/4/sc17_055_02_8McClure, M., Tarr, P., Thompson, C. M., & Eckhoff, A. (2017). Defining quality in visual art education for young children: Building on the position statement of the early childhood art educators. Arts Education Policy Review, 118(3), 154–163. https://doi.org/10.1080/10632913.2016.1245167Mishra, L. (2016). Focus Group Discussion in Qualitative Research. TechnoLearn: An International Journal of Educational Technology, 6(1), 1. https://doi.org/10.5958/2249-5223.2016.00001.2Monhardt, L., & Monhardt, R. (2006). Creating a context for the learning of science process skills through picture books. Early Childhood Education Journal, 34(1), 67–71. https://doi.org/10.1007/s10643-006-0108-9Monsalvatge, L., Long, K., & DiBello, L. (2013). Turning our world of learning inside out! Dimensions of Early Childhood, 41(3), 23–30.Moomaw, S. (2012). STEM begins in the early years. School Science & Mathematics, 112(2), 57–58.Moomaw, S. (2016). Move Back the Clock, Educators: STEM Begins at Birth. School Science & Mathematics, 116(5), 237–238.Moomaw, S., & Davis, J. A. (2010). STEM Comes to Preschool. Young Cihildren, 12–18(September), 12–18.Munawar, M., Roshayanti, F., & Sugiyanti. (2019). Implementation of STEAM (Science, Technology, Engineering, Art, Mathematics)-Based Early Childhood Education Learning in Semarang City. Jurnal CERIA, 2(5), 276–285.National Research Council. (1996). National Science Education Standards. Washington, DC: National Academy of Sciences.Nicholson, S. (1972). The Theory of Loose Parts: An important principle for design methodology. Studies in Design Education Craft & Technology, 4(2), 5–12.O.Nyumba, T., Wilson, K., Derrick, C. J., & Mukherjee, N. (2018). The use of focus group discussion methodology: Insights from two decades of application in conservation. Methods in Ecology and Evolution, 9(1), 20–32. https://doi.org/10.1111/2041-210X.12860Padilla-Diaz, M. (2015). Phenomenology in Educational Qualitative Research : Philosophy as Science or Philosophical Science ? International Journal of Educational Excellence, 1(2), 101–110.Padilla, M. J. (1990). The Science Process Skills. Research Matters - to the Science Teacher, 1(March), 1–3.Park, D. Y., Park, M. H., & Bates, A. B. (2018). Exploring Young Children’s Understanding About the Concept of Volume Through Engineering Design in a STEM Activity: A Case Study. International Journal of Science and Mathematics Education, 16(2), 275–294. https://doi.org/10.1007/s10763-016-9776-0Rahardjo, M. M. (2019). Implementasi Pendekatan Saintifik Sebagai Pembentuk Keterampilan Proses Sains Anak Usia Dini. Scholaria: Jurnal Pendidikan Dan Kebudayaan, 9(2), 148–159. https://doi.org/10.24246/j.js.2019.v9.i2.p148-159Robison, T. (2016). Male Elementary General Music Teachers : A Phenomenological Study. Journal of Music Teacher Education, 26(2), 77–89. https://doi.org/10.1177/1057083715622019Rocha Fernandes, G. W., Rodrigues, A. M., & Ferreira, C. A. (2018). Conceptions of the Nature of Science and Technology: a Study with Children and Youths in a Non-Formal Science and Technology Education Setting. Research in Science Education, 48(5), 1071–1106. https://doi.org/10.1007/s11165-016-9599-6Sawyer, R. K. (2006). Educating for innovation. 1(2006), 41–48. https://doi.org/10.1016/j.tsc.2005.08.001Sharapan, H. (2012). ERIC - From STEM to STEAM: How Early Childhood Educators Can Apply Fred Rogers’ Approach, Young Children, 2012-Jan. Young Children, 67(1), 36–40.Siantayani, Y. (2018). STEAM: Science-Technology-Engineering-Art-Mathematics. Semarang: SINAU Teachers Development Center.Sikder, S., & Fleer, M. (2015). Small Science : Infants and Toddlers Experiencing Science in Everyday Family Life. Research in Science Education, 45(3), 445–464. https://doi.org/10.1007/s11165-014-9431-0Smith-gilman, S. (2018). The Arts, Loose Parts and Conversations. Journal of the Canadian Association for Curriculum Studies, 16(1), 90–103.Sohn, B. K., Thomas, S. P., Greenberg, K. H., & Pollio, H. R. (2017). Hearing the Voices of Students and Teachers : A Phenomenological Approach to Educational Research. Qualitative Research in Education, 6(2), 121–148. https://doi.org/10.17583/qre.2017.2374Strong-wilson, T., & Ellis, J. (2002). Children and Place : Reggio Emilia’s Environment as Third Teacher. Theory into Practice, 46(1), 40–47.Sutton, M. J. (2011). In the hand and mind: The intersection of loose parts and imagination in evocative settings for young children. Children, Youth and Environments, 21(2), 408–424.Tippett, C. D., & Milford, T. M. (2017). Findings from a Pre-kindergarten Classroom: Making the Case for STEM in Early Childhood Education. International Journal of Science and Mathematics Education, 15, 67–86. https://doi.org/10.1007/s10763-017-9812-8Tippett, C., & Milford, T. (2017). STEM Resources and Materials for Engaging Learning Experiences. International Journal of Science & Mathematics Education, 15(March), 67–86. https://doi.org/10.1007/s10763-017-9812-8Veselack, E., Miller, D., & Cain-Chang, L. (2015). Raindrops on noses and toes in the dirt: infants and toddlers in the outdoor classroom. Dimensions Educational Research Foundation.Yuksel-Arslan, P., Yildirim, S., & Robin, B. R. (2016). A phenomenological study : teachers ’ experiences of using digital storytelling in early childhood education. Educational Studies, 42(5), 427–445. https://doi.org/10.1080/03055698.2016.1195717